Introducing a Regulatory Policy Framework of Bait Fishing in European Coastal Lagoons: The Case of Ria de Aveiro in Portugal - Xenarios, Stefanos; Queiroga, Henrique; Lillebø, Ana I.; Aleixo, Ana (Fishes, 2018)
The harvesting of bait through digging in coastal mudflats is practiced for recreational and commercial purposes in European coastal systems including the Ria de Aveiro coastal lagoon on the northwest Atlantic coast of Portugal. The scale of harvesting in the Ria de Aveiro has recently increased due to the current economic climate in Portugal, with targeting of the polychaete, Diopatra neapolitana species or “casulo” as it is widely known in the Aveiro region. The national authorities have attempted to control casulo digging by issuing a regulation (Ordinance) in 2014 on the maximum daily catch limit to be caught by each individual. The daily catch limit is intended to represent the Maximum Sustainable Yield (MSY) for casulo beyond which overfishing will occur. The monitoring of the regulatory measures is expected to be conducted through on-site inspections in the digging areas. However, weak law enforcement was noticed, while there is also controversy over the daily catch limit (quota) stipulated by the Ordinance. To this end, the current study attempted to assess digging activities through remote monitoring and random inspections for a better policy enforcement of the national regulation. In addition, different harvesting scenarios were employed through a simplified bioeconomic model to attribute the current and future harvesting trends of bait digging in Aveiro coastal lagoon. The study findings indicate that remote monitoring coupled with some onsite interviews could be a more effective approach for the implementation of the current bait digging policy. Further, the results point to a distinctive discrepancy between the daily catch amount (MSY) introduced by the national legislation and the study findings which should be further scrutinized. The diggers seem to have reached the sustainable harvest identified by the present research. The current economic hardship in Portugal and the low profitability in similar employment sectors will possibly attract more diggers and increase harvesting in the near future. An increased harvest would likely trigger overfishing of D. neapolitana with unknown consequences for the population of the species as well as the aquatic ecosystem. The socio-economic and environmental effects are yet to be further clarified with more detailed data and advanced modeling techniques to ensure the sustainability of the activity.
Keywords: lagoons; catch estimate; catch per unit effort; bioeconomic modeling; management scenarios; Diopatra neapolitana; Portugal